PESANTREN IDEOLOGY AND MANAGEMENT PATTERNS ON THE EFFECTIVENESS OF PESANTREN KILAT PROGRAMS - Firmansah, Rizal Fikri; Fahrurrozi (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
Studies on the effectiveness of pesantren kilat (short-term Islamic boarding programs) from the perspectives of ideology and pesantren management remain limited, especially in comparative contexts between modern and traditional pesantren. Pesantren kilat aim to enhance students' religious understanding and cultivate Islamic character. However, differences in ideological orientation and managerial approaches significantly affect the implementation of these programs. This study examines the management of pesantren kilat at the Islamic Centre Bin Baz Boarding School in Wangon, Banyumas (Salafi-modern) and the Al-Ishlah Boarding School in Mangkang, Semarang (Aswaja-traditional). Using a descriptive qualitative method with a comparative approach, data were collected through interviews, observations, and document analysis. The findings reveal that Bin Baz implements systematic, technology-based planning, flexible organizational structures, and adaptive execution with informal communication. Program evaluation is conducted strictly by coordinators. In contrast, Al-Ishlah applies tradition-based planning directed by the kyai, hierarchical organization emphasizing obedience, charismatic leadership in program implementation, and traditional evaluation methods through sorogan and bandongan. These findings confirm that ideological and managerial differences shape program effectiveness. The study recommends the optimization of technology and the adoption of data-driven evaluation methods to enhance the quality of pesantren kilat programs.